Eczema herpeticum in a patient with atopic dermatitis, coxsackie B virus, and staphylococcal infection: A double skin damage - Andrea D Pratico; Valentina Fatuzzo; Maria Elena Cucuzza; Flavia M C La Mendola (Wolters Kluwer Medknow Publications, 2018)
Eczema herpeticum is a rare viral skin scattered infection whose main etiologic agents are HSV1-2 and coxsackievirus, but its association with atopic dermatitis suggests that different factors may play a role in this complex phenotype. When not promptly treated, it can spread to other organs, causing severe complications such as keratoconjunctivitis, encephalitis, and meningitis. We describe the case of a patient with atopic dermatitis who came to our observation presenting with diffuse purulent vesicular lesions, whose bacterial culture was positive for Staphylococcus aureus and whose serologic examinations showed IgM positivity for coxsackie B virus.